2007
DOI: 10.1111/j.1939-1676.2007.tb03067.x
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Component as an Indicator of Platelet Activation in Foals and Adult Horses

Abstract: Background: Mean platelet component (MPC) is a new platelet variable, measured by modern commercial complete blood count analyzers, that is reduced during platelet activation in humans and small animals.Hypothesis: MPC decreases in horses with clinical conditions that cause platelet activation and disseminated intravascular coagulation (DIC).Animals: We obtained 418 CBCs from 100 sick and 20 healthy neonates and 178 sick and 45 sound adult horses. Sick neonates were classified into septic and nonseptic, and DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…In the present study, fibrin deposits were observed in 87.5% of the nonsurviving septic foals when using the IHC technique. This percentage is slightly higher than those reported in some in vivo studies 1,23 that reported a diagnosis of DIC in 50% of septic foals during hospitalization. However, a higher percentage of foals that did not survive were diagnosed with DIC.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In the present study, fibrin deposits were observed in 87.5% of the nonsurviving septic foals when using the IHC technique. This percentage is slightly higher than those reported in some in vivo studies 1,23 that reported a diagnosis of DIC in 50% of septic foals during hospitalization. However, a higher percentage of foals that did not survive were diagnosed with DIC.…”
Section: Discussionsupporting
confidence: 82%
“…17,37,38 The most relevant finding of the present study is that most nonsurviving septic foals had fibrin deposits in their tissues, specially demonstrated by IHC, and systemic fibrin deposition is consistent with the postmortem diagnosis of DIC. Even considering only the nonsurviving septic foals, this finding is consistent with our clinical impression and the results of other previous in vivo studies 1,24 that nonsurviving septic foals have some hemostatic abnormalities despite the paucity of reported cases in the veterinary literature. In the present study, fibrin deposits were observed in 87.5% of the nonsurviving septic foals when using the IHC technique.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations